The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/nbm.4054
|View full text |Cite
|
Sign up to set email alerts
|

Cancer metabolism in a snapshot: MRS(I)

Abstract: The contribution of MRS(I) to the in vivo evaluation of cancer-metabolism-derived metrics, mostly since 2016, is reviewed here. Increased carbon consumption by tumour cells, which are highly glycolytic, is now being sampled by 13 C magnetic resonance spectroscopic imaging (MRSI) following the injection of hyperpolarized [1-13 C] pyruvate (Pyr). Hot-spots of, mostly, increased lactate dehydrogenase activity or flow between Pyr and lactate (Lac) have been seen with cancer progression in prostate (preclinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 154 publications
(227 reference statements)
0
12
0
Order By: Relevance
“…We have described the non-invasive assessment of response to therapy in preclinical GL261 GB (control and under TMZ therapy) with magnetic resonance spectroscopic imaging (MRSI) approaches. MRSI combines anatomical information from magnetic resonance imaging (MRI) [ 26 ], and magnetic resonance spectroscopy (MRS), which provides information regarding the metabolomic profile of the investigated tissue [ 27 , 28 , 29 ]. When using MRSI is coupled to advanced machine learning analysis (source extraction as described in [ 30 ]), spectral pattern differences between actively proliferating GB and GB responding to therapy can be shown colour-coded (the nosological images) in single-slice [ 23 ] or multislice volumetric approaches [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have described the non-invasive assessment of response to therapy in preclinical GL261 GB (control and under TMZ therapy) with magnetic resonance spectroscopic imaging (MRSI) approaches. MRSI combines anatomical information from magnetic resonance imaging (MRI) [ 26 ], and magnetic resonance spectroscopy (MRS), which provides information regarding the metabolomic profile of the investigated tissue [ 27 , 28 , 29 ]. When using MRSI is coupled to advanced machine learning analysis (source extraction as described in [ 30 ]), spectral pattern differences between actively proliferating GB and GB responding to therapy can be shown colour-coded (the nosological images) in single-slice [ 23 ] or multislice volumetric approaches [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…al. wherein they suggest that Lac/Bic might be a better metric for assessing cancer metabolism [18]. Prior cross-sectional hyperpolarized 13 C MRS studies demonstrated a consistent decrease in Lac/Bic ratios within three hours of anti-vascular endothelial growth factor (anti-VEGF) therapy in a glioblastoma (GBM) rodent model, with a spread in Lac/Bic values over the next 48 hrs suggesting this effect reverses at differential rates [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, brain metabolism plays a major role in pathogenesis of some neurological disorders such as Alzheimer’s disease 17 - 19 by hypometabolismpromoted Aβ deposition. 20 Furthermore, the findings based on proton magnetic resonance spectroscopy have shown the alteration of metabolite concentration in various areas of the brain in different neurometabolic disorders such as multiple sclerosis, 21 brain tumors, 22 , 23 epilepsy, 24 , 25 Alzheimer disease, 26 - 28 and dementia 29 is significantly correlated with cognitive decline. Based on the abovementioned studies, metabolic diseases of the brain can lead to changes in the structure and function of brain areas associated with cognition; most metabolic diseases of the brain cause changes in neuronal structure and cognitive decline.…”
Section: Cognitive Changes In Metabolic Syndromementioning
confidence: 99%